Mixed-methods cross-sectional study of the prevention of vertical HIV transmission program users unaware of male partner's HIV status, in six South African districts with a high antenatal HIV burden - Tshiamo M. Mmotsa; Vuyolwethu Magasana; Duduzile F. Nsibande; Mbongeleni Buthelezi; Reshmi Dassaye; Violeta J. Rodriguez; Deborah L. Jones; Ameena E. Goga; Nobubelo K. Ngandu (BMC, 2023)
Abstract Background Elimination of vertical HIV Transmission (VHT) and maternal deaths are global health priorities. Male involvement is one of the most important factors that influences women's decisions, including the uptake of Prevention of vertical HIV transmission (P-VHT). We sought to understand not knowing a male partner's HIV status (MPHIVs) amongst women using services to prevent vertical HIV transmission in six South African districts with high antenatal HIV burden. Methods A mixed-methods cross-sectional study was conducted in six South African districts, and data collected through face-to-face interviews with women and focus group discussions (FGDs) with women or male partners. The quantitative data were analyzed using STATA SE-17.0 and an inductive approach was used for qualitative data analysis. Results Overall, 28.7% of women were unaware of their MPHIVs, while 25.3% and 46.0% knew the MPHIVs was positive or negative, respectively. In multivariable logistic regression, single marital status and unplanned pregnancy increased the odds of not knowing a MPHIVs while a woman's disclosure of her HIV status to the male partner reduced the odds. FDGs highlighted complexities around MPHIVs disclosure, e.g., reluctance to test for HIV and potential interventions including healthcare worker (HCW) assisted HIV disclosure. Conclusion User-informed interventions to address MPHIVs non-disclosure amongst women of child-bearing age, particularly those at risk of unstable sexual partners and unplanned pregnancies, should be strengthened.